Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2008
DOI: 10.1371/journal.pone.0002861
|View full text |Cite
|
Sign up to set email alerts
|

A Randomised Trial of an Eight-Week, Once Weekly Primaquine Regimen to Prevent Relapse of Plasmodium vivax in Northwest Frontier Province, Pakistan

Abstract: BackgroundVivax malaria remains a major cause of morbidity in the subtropics. To undermine the stability of the disease, drugs are required that prevent relapse and provide reservoir reduction. A 14-day course of primaquine (PQ) is effective but cannot safely be used in routine practice because of its interaction with glucose-6-phosphate dehydrogenase (G6PD) deficiency for which testing is seldom available. Safe and effective use of PQ without the need for G6PD testing would be ideal. The efficacy and safety o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
84
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 71 publications
(85 citation statements)
references
References 27 publications
(36 reference statements)
1
84
0
Order By: Relevance
“…• 0.25 mg/kg/day for 14 days: it the standard procedure, here called 210- 14, referring to what in an adult weighting 60 kg corresponds to 210 mg of TD in 14 days; • 0.50 mg/kg/day for 7 days: is the standard TD but administered in 7 days; scheme 210-7; • 1.17 mg/mg/day for 3 days: the standard TD given in 3 days; scheme 210-3; • 0.25 mg/kg/day for 3, 5, 7, 9 or 10 days: each one corresponds to the same daily doses of the standard scheme but with lower TD tan the standard one, supplying between 45 and 150 mg of TD in 3 to 10 days (including here a study which administered 45 mg in a single dose (meaning, in 1 day); scheme 45 to 150 (in 3 to 10), noting that here it is included a study which gave 150 in 5 days, i.e., 30mg per day; • 0.75 mg/kg/day for 1 day a week and for 8 weeks 26 (a report): equivalent to 360 mg of TD, which is 71% higher than the standard TD (210 mg) but with very low daily doses [6,4 mg/day instead of 15 mg/day in an adult of 60 kg]); is included in the group 210-14; We proceeded into grouping the studies according to their objectives (to compare the anti-recurrence effectiveness of TDs of PQ given a fixed amount of time). The result were these 4 schemes of treatment in relation to the TD of PQ and the days in which this TD was used TD: 210 mg in 14 days; 210 mg in 7 days; 45 to 150 mg in 3 to 10 days; and 0 mg (not used).…”
Section: Resultsmentioning
confidence: 99%
“…• 0.25 mg/kg/day for 14 days: it the standard procedure, here called 210- 14, referring to what in an adult weighting 60 kg corresponds to 210 mg of TD in 14 days; • 0.50 mg/kg/day for 7 days: is the standard TD but administered in 7 days; scheme 210-7; • 1.17 mg/mg/day for 3 days: the standard TD given in 3 days; scheme 210-3; • 0.25 mg/kg/day for 3, 5, 7, 9 or 10 days: each one corresponds to the same daily doses of the standard scheme but with lower TD tan the standard one, supplying between 45 and 150 mg of TD in 3 to 10 days (including here a study which administered 45 mg in a single dose (meaning, in 1 day); scheme 45 to 150 (in 3 to 10), noting that here it is included a study which gave 150 in 5 days, i.e., 30mg per day; • 0.75 mg/kg/day for 1 day a week and for 8 weeks 26 (a report): equivalent to 360 mg of TD, which is 71% higher than the standard TD (210 mg) but with very low daily doses [6,4 mg/day instead of 15 mg/day in an adult of 60 kg]); is included in the group 210-14; We proceeded into grouping the studies according to their objectives (to compare the anti-recurrence effectiveness of TDs of PQ given a fixed amount of time). The result were these 4 schemes of treatment in relation to the TD of PQ and the days in which this TD was used TD: 210 mg in 14 days; 210 mg in 7 days; 45 to 150 mg in 3 to 10 days; and 0 mg (not used).…”
Section: Resultsmentioning
confidence: 99%
“…It is not clear if any such variation in the genetic background of this population could account for this observation. In addition, it has been shown that when higher doses of PQ, such as 0.5 mg/kg for 14 days, are used as recommended by the CDC (53), lower incidences of recurrence are reported (between 1.9% and 6.6% during 180 to 365 days) (43,54,55). However, no direct comparison had been made between a PQ regimen of 0.5 mg/kg for 14 days and the standard regimen in countries where malaria is endemic (9).…”
Section: Discussionmentioning
confidence: 99%
“…Park and Kang (162) measured only a 32% effectiveness of postexposure presumptive therapy with the 15-mg daily (14-day) regimen for tens of thousands of soldiers from the Republic of Korea. The 30-mg daily (14-day) regimen achieved 94% efficacy in the northwestern frontier of Pakistan (135), whereas a supervised regimen of 15 mg daily achieved only 48% efficacy in the first 3 months in the same region (133). Another study in the same region recorded a 35% efficacy for that regimen (187 Risk of reinfection may confound these studies from India, Pakistan, and Afghanistan with long-term follow-up (9 to 12 months).…”
Section: Distributionmentioning
confidence: 99%